2021
DOI: 10.1017/s0007114521000854
|View full text |Cite
|
Sign up to set email alerts
|

Eating context and ultraprocessed food consumption among UK adolescents

Abstract: This study aimed to evaluate the association between eating context patterns and ultra-processed food consumption at two main meal occasions in a representative sample of UK adolescents. Data was acquired from four-day food records of adolescents aged 11–18 years, who participated in the 2014–2016 UK National Diet and Nutrition Survey (n=542). The eating context was assessed considering the location of the meal (lunch and dinner) occasion, the individuals present, whether the television was on and if the food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 75 publications
(116 reference statements)
1
22
0
1
Order By: Relevance
“…Similar findings were observed both intra- and inter-country. The highest levels of consumption were observed in the United States and the United Kingdom with the percent of energy intake generally higher than 50% with respect to TEI [ 18 , 19 , 36 , 38 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Conversely, the lowest levels were observed in Italy, in which the two studies identified reported about 10% energy obtained from UPF [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were observed both intra- and inter-country. The highest levels of consumption were observed in the United States and the United Kingdom with the percent of energy intake generally higher than 50% with respect to TEI [ 18 , 19 , 36 , 38 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Conversely, the lowest levels were observed in Italy, in which the two studies identified reported about 10% energy obtained from UPF [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…On average, the age of participants was 38.9 years, although half of the studies did not report this information. Fifteen studies focused only on children [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], seven on adolescents [31][32][33][34][35][36][37], five on pregnant women [38][39][40][41][42], and three on older subjects [43][44][45], whereas others focused on an adult population or on 2 target groups. Overall, 58.8% of participants were women.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Second, it matters for the continued understanding of the social functions of eating together among children and adolescents, beyond the contexts of the family and school, that are otherwise commonly studied. In fact, adolescents’ eating with friends outside the family environment has been associated with consumption of ultra-processed foods [ 70 ], while their friendship ties are associated with both unhealthy food habits [ 71 ] and body weight [ 72 ]. In sum, as children grow and mature their parents have less and less influence over their eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that, among British children and adolescents, the consumption of ultraprocessed foods was influenced by eating contexts, such as the presence of other people and the location [15,18]. In this way, the present study aims to analyse the association between different places of consumption and the intake of ultra-processed foods in the United Kingdom in 2014-2016.…”
Section: Accepted Manuscriptmentioning
confidence: 94%